Taxonomic re-evaluation of the enigmatic Pyrus magyarica (Rosaceae) - Barina, Zoltán; Király, Gergely (Phytotaxa, 2014)
Pyrus magyarica was considered as a “superendemic” species of the Carpathian Basin for a long time; however, despite its presumed significance, doubts about its taxonomical status have been raised. The confusions originate from the invalidity of the description and the lack of type material. Latter interpretations are not consistent and contradict the description of the species in the protologue. The authors attempted to get access to the original material of the taxon, but no vouchers or living specimens that correspond to the protologue were found; herbarium specimens assigned as P. magyarica mostly refer to P. pyraster. Based on the available records, P. magyarica cannot be clearly defined and re-described; thus we propose to leave off the use of the name P. magyarica as it has no clear content.